The efficacy of suppository versus oral ibuprofen for reducing fever in children - Suhesti Handayani; Sri Rezeki Hadinegoro; Sudigdo Sastroasmoro (Indonesian Pediatric Society, 2005)
Background Ibuprofen suppository is used to reduce fever inchildren who are unable to receive it orally. The effectiveness ofibuprofen suppository compared to that of oral ibuprofen has notbeen documented in Indonesian children.Objective The aim of this study was to compare the efficacy ofibuprofen suppository with that of oral ibuprofen for reducingfever in children.Methods This study was a randomized clinical trial without blind-ing on children aged 2-5 years with body weight of 12.5 to 16 kgwho had fever. Subjects received ibuprofen in either oral (7.5mg/kg) or suppository (125 mg) form. The temperature was mea-sured prior to ibuprofen administration, 30 minutes afterwards,and every subsequent half hour until the end of the sixth hour.Any observed adverse effects were recorded.Results Mean time needed for fever reduction was 2.72 (SD 1.1)hours in the suppository group, compared to 3.43 (SD 0.9) hoursin the oral group (P=0.004). The mean rate of fever reduction inthe suppository group was 0.90 (SD 0.4) °C/hour, while in theoral group it was 0.61 (SD 0.3) °C/hour. However, mean maxi-mum temperature lowering ability did not differ significantly [2.11(SD 0.7) °C for the suppository group and 1.99 (SD 0.7) °C, forthe oral group (P=0.489)]. There was no significant difference inmean duration of effect [220.8 (SD 83.0) hours for the supposi-tory group and 196.6 (SD 92.7) hours for the oral group (p=0.231)].Conclusions There was no significant difference between bothpreparations in maximum temperature lowering ability and dura-tion of effect. Temperature reduction was significantly fasterwith the administration of ibuprofen suppository